Autonomous Rail Rapid Transit (ART) Prototype Concept Using Wireless Charging System with Electromagnetic Induction Coupling - Sunardi sunardi; Reyvaldy Raffli Bachtiar; Alcha Duta Septione; Niken Ayu Larasati; Dimas Adi Perwira; Feddy Setio Pribadi; Muhammad Nurtanto; Tamil Selvan Subramaniam; Soedibyo (Journal of Railway Transportation and Technology, 2022)
The development of charging technology in Autonomous Rapit Rail Transit (ART) vehicles uses a wireless power system by optimizing. The selection of the power transfer method uses an Inductive coupling of the LCCL model with a wide variation in the cross-section of the wire and the diameter of the fixed coil. Scenario testing by installing a power transfer system on ART facilities, testing is carried out on coil inductance, resonance coupling gap and power efficiency. Optimum power transfer is obtained on coils with a cross-sectional area of 1.5 mm / 6.13 μH and the highest power transfer efficiency of 40% at a distance of 0.5cm.